1968
DOI: 10.1111/j.1432-1033.1968.tb00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Studies on Liver Alcohol Dehydrogenase

Abstract: The rate of reaction of liver alcohol dehydrogenase with iodoacetamide is independent of pH between pH 6-10. Orthophenanthroline, ADP-ribose and ADP protect the enzyme against alkylation. For iodoacetate, the rate of alkylation decreases with increasing pH over the range 7-9 and reflects the titration of a group with a p K of 7.9. Imidazole enhances the rate of alkylation by both iodoacetamide and iodoacetate and renders the rate of alkylation by iodoacetate pH independent. The interactions of ADP-ribose and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 18 publications
(12 reference statements)
4
26
0
Order By: Relevance
“…from horse liver forms highly-fluorescent complexes with NADH and imidazole [ 1 ] . Enhancement of fluorescence of enzyme-bound NADH was used to estimate dissociation constants of binary and ternary complexes, at pH values of 6,7,8 and 9. lmidazole also stimulates inactivation of the enzyme by iodoacetate [2,31 ; dissociation constants of the binary enzyme-imidazole complex were calculated at pH 7.2 and 9.0, and 7.4 and 10.0, respectively. These two methods gave similar values in the pH region 7 ~ 8, but the discrepancy at pH 9 was considerable.…”
Section: Introductionmentioning
confidence: 99%
“…from horse liver forms highly-fluorescent complexes with NADH and imidazole [ 1 ] . Enhancement of fluorescence of enzyme-bound NADH was used to estimate dissociation constants of binary and ternary complexes, at pH values of 6,7,8 and 9. lmidazole also stimulates inactivation of the enzyme by iodoacetate [2,31 ; dissociation constants of the binary enzyme-imidazole complex were calculated at pH 7.2 and 9.0, and 7.4 and 10.0, respectively. These two methods gave similar values in the pH region 7 ~ 8, but the discrepancy at pH 9 was considerable.…”
Section: Introductionmentioning
confidence: 99%
“…Evans and Rabin [2] showed that AMP and ADP protected liver alcohol dehydrogenase from iodoacetate. As shown in Figs.l and 2, protection by AMP, ADP, ATP, GMP and ADP-ribose is competitive with iodoacetate.…”
Section: Adenine Nucleotidesmentioning
confidence: 99%
“…These neutral ligands may be producing conformational changes which affect the active site of the enzyme. The acceleration of the inactivation of the enzyme by iodoacetate in the presence of excess imidazole has been considered due to a conformational change induced by imidazole [28,4]. Such conformational changes may protect the active-centre lysine from pyridoxal-P.…”
Section: The Effect Of Coenzyme and Inhibitors On The Enhancement Of mentioning
confidence: 99%